Application of evolutionary programming to optimal siting and sizing and optimal scheduling of distributed generation - Roncesvalles, Jose Carlos K. (2008)
Evolutionary programming (EP) is a global optimization method that can be applied to complex optimization problems such as Distributed Generation (DG) Sizing and Siting as well as Scheduling. The distribution system is modeled using a loadflow formulation where DG is modeled as injected real and reactive power. EP is implemented by perturbing DG outputs and evaluating the fitness values of the resulting systems. Optimal locations and sizes of DG's are determined using a fitness value based on system loss reduction while an optimal DG schedule is determined for a 24 hour period using a fitness value based on energy cost. A Mathematical model is developed to represent different types of loads within the distribution system and different types of energy sources were represented based on their availability and cost. Spot market prices were modeled based on a typical 24 hour price curve. EP is shown to be a robust optimization method that is able to integrate variations such decision variables needed in optimizing multiple DG locations/sizes within a distribution system.